Kant and the Role of Human Sensibility in Animal Welfare; [Kant y el Rol de la Sensibilidad Humana en el Bienestar Animal] - Chapsal-Escudero, M (Pontifica Universidad Catolica del Peru, 2024)
Kant and the Role of Human Sensibility in Animal Welfare”. This paper attempts to show that, according to Kant, though we human beings have only indirect duties towards non-human animals, this is enough to ground a strong defense of their welfare and protection as sentient beings. To this end, the paper addresses Kant’s analogy between animal nature and human nature. It also shows how human sensibility –through the feelings of compassion and sympathy– is essential for the fulfillment of our indirect duty of safeguarding animal welfare. © 2024 Pontifica Universidad Catolica del Peru. All rights reserved.